CONSUMER PROTECTION AGAINST DIFFERENT PRICE TAGS AT THE INDOMARET MATANG GLUMPANGDUA CASHIER IN THE REVIEW OF LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION - Ade Soraya; Dian Eriani; Riska Maulizar (RADJA PUBLIKA, 2023)
Cases of price differences, forms that are too small or difficult to see by consumers, differences in price labels and receipt prices at the checkout, price placement that does not match the goods, writing that is blurry so that it is difficult to read are usually considered less important, but this is actually very detrimental and has violated Law Number 8 of 1999 concerning Consumer Protection. If it is related to Law Number 8 of 1999 concerning Consumer Protection in Article 4 letter (b) it is clearly stated that one of the consumer rights is the right to choose goods and services and obtain goods and services according to value and guarantee. From the results of observations made by researchers at Indomaret Matang Glumpang Dua, it was found that there are cases of differences in price tags and cashier prices, this can make consumers stuck with price tags with the price paid, our people's habits are not careful about refunds or looking back at the price list from the payment receipt , although there are no complaints from consumers regarding the price difference, this may be due to the low level of consumer accuracy or the habit of conducting traditional transactions. Errors on the price tag with the price list on the payment counter machine often occur at the Indomaret Matang Glumpangdua Minimarket, where the price listed and when paying for the difference is due to inaccurate administration, with price changes that occur too often following instructions from PT. Indomarco Prismatama will hereby cause a price difference.